Corrosion resistance of steel embedded in sulfoaluminate-based binders. (April 2018) - Carsana, Maddalena; Canonico, Fulvio; Bertolini, Luca
Abstract: The use of new binders for structural concrete raises questions about the durability of reinforced concrete structures. Calcium sulfoaluminate cement (CSA) has become in recent years an environmentally-friendly alternative to ordinary Portland cement (OPC), but the protection capacity of CSA concrete in relation to the corrosion of embedded steel reinforcement needs to be studied. This paper describes a study on the corrosion behaviour of carbon steel embedded in concrete made with CSA-based binders. It is shown that the pore solution of sulfoaluminate concrete was sufficiently alkaline to passivate embedded carbon steel rebars. Compared to traditional Portland and Portland-limestone cements, CSA cement led to higher carbonation rate of concrete, but to lower corrosion rate of steel in carbonated concrete, likely due to the higher electrical resistivity. Corrosion rate was negligible up to 95% RH at 20 °C. Blending of CSA and OPC cements improved steel passivity and concrete resistance to carbonation.